The Aesthetic Communication: Representation of Gandrung Bangun Urip Dance in Batukandik Village - Haes, Putri Ekaresty; Apsari, Ayu Made Dwi (Universitas Negeri Medan, 2023)
The Gandrung Bangun Urip dance is one of the tarekat's sacred traditions from Banjar Bangun Urip, Batukandik Village, Nusa Penida, which is still performed in several manusa nyadnya events. This research aims to describe representation rates based on communication aesthetics. This qualitative research uses an ethnographic communication approach based on the results of participatory observation, in-depth interviews and documentation. The data obtained were analyzed using data triangulation techniques. The results obtained from the research conducted on the Banjar Batukandik krama are the Gandrung Bangun Urip dance, which represents the expression of gratitude for Krama Banjar and a symbol of repelling reinforcements or disasters. The representation of this dance is a cultural agreement in a social context as the embodiment of philosophy in society, namely Tri Hitakarana, Rwa Bhineda so that apart from having a religious function, it also has a social function, namely forming harmonious community relations within the community.